Analysis of risks in the tank cleaning activity of a storage and fuel distribution company of Governador Valadares City (Research, Society and Development, 2020)
The internal cleaning of fuel storage tanks involves great risk, since it is carried out in a confined space. This type of activity is carried out in a fuel storage and distribution company in Governador Valadares-MG. In order to guide the cleaning of the storage tanks, the company prepared a manual of procedures that discusses the risks of the activity. In this context, this study aimed to analyze the cleaning procedures manual, in order to verify if it predicts and addresses all risks related to the activity. The analysis of this material showed that only five out of ten risks inherent to the tank cleaning activity are addressed in the manual, and three out of those five have preventive measures. The absence of other risks in the manual can compromise the proper and safe cleaning of the tanks. This study revealed the need to change the manual used by the company, in order to foresee all the risks to which workers are exposed, as well as provide preventive and control measures, in compliance with current regulatory standards, in order to provide a safer work environment.